Simulink/MATLAB code of simulation of L-1 adaptive control for a quadrotor subject to actuator faults - Whidborne, James F. (Cranfield University, 2022)
Simulink/MATLAB code of simulation of L-1 adaptive control for a quadrotor subject to actuator faults. QuadrotorL1initialize.m - Initialize Simulink code for simulation of L_1 adaptive control of a quadrotor QuadrotorL1adaptive.slx - Simulink code for simulation of L_1 adaptive control of a quadrotor QuadrotorLQRIinitialize.m - Initialize Simulink code for simulation of baseline LQR controller + integral action for a quadrotor QuadrotorLQRI.slx - Simulink code for simulation of baseline LQR controller + integral action for a quadrotor Additional codes can be downloaded from l1-adaptive-control-tutorials Please acknowledge and reference via: D. Xu, J.F. Whidborne and A. Cooke. Fault tolerant control of a quadrotor using L-1 adaptive control. International Journal of Intelligent Unmanned Systems.4(1):43-66, 2016. (doi:10.1108/IJIUS-08-2015-0011)
Keywords: Fault tolerant control,'; 'UAV control'; 'L-1 adaptive control'; 'LQR control'; 'quadrotor drones'; 'Rotor failure'